The investigation of the effect of relevant parameters of Mongolian natural zeolites for ammonium ion removal from aqueous solution - Dashnyam Munkhjargal; Jamsranjav Ganbaatar (Zaštita Materijala)
Our study investigated the potential of natural tseolite for ammonium ions removal from aqueous solution. In batch study, the effect of relevant parameters such as pH, adsorbent dosage, contact time and initial ammonium concentration. Also, the effect pH investigated on ammonium removal of aqueous solutions. The removal capacity of clinoptilolite increased by 15 minutes during our experiment. The Langmuir and Freundlich model were applied to describe the equilibrium isotherms for ammonium uptake and the Freundlich model agree very well with experimental data. Based on the results, it can be concluded that the natural zeolite is suitable for removal of NH4+ ions wastewater.